Adventures in the Chemistry of 1,1-Diacylcyclopropanes - Langer, Peter (Synlett, 2023)
The present personalized account aims to highlight 1,1-diacylcyclopropanes as synthetic building blocks or target molecules. The chemistry presented includes cyclization reactions of 1,1-diacylcyclopropanes with free and masked dianions to give spirocyclopropanes as products or reactive intermediates that readily undergo ring-cleavage reactions. In addition, the synthesis of cyclopropylated 1,3,5-tricarbonyl compounds, containing two 1,1-diacylcyclopropane moieties, is discussed. Based on this work also other syntheses of cyclopropanes were developed.1 Introduction2 Reactions of Masked Dianions3 Reactions of Free Dianions4 Cyclopropylated 1,3,5-Tricarbonyl Compounds5 Miscellaneous6 Conclusions
Keywords: cyclopropanes; cyclizations; dianions; regioselectivity; silyl enol ethers